Physical Properties and Chemical Characterization of Two Experimental Epoxy Resin Root Canal Sealers - Ashraf, Hengameh; Najafi, Farhood; Heidari, Soolmaz; Mohammadian, Manijeh; Zadsirjan, Saeede (Iranian Endodontic Journal, 2017)
Introduction: The aim of this in vitro study was to evaluate the setting time, flow, film thickness, solubility, radiopacity and characterization analysis of three epoxy resin based sealers including two experimental sealers and AH-26. Methods and Materials: Five samples of each material were evaluated for setting time, flow, film thickness, solubility and radiopacity according to ISO 6876 Standard. Characterization of sealers was performed under the scanning electron microscopy (SEM), X-ray energy dispersive spectroscopy, X-ray diffraction (XRD) and Fourier transform infrared (FTIR) spectroscopy. Statistical evaluation was performed using the Kruskal-Wallis test. Results: In this study, AH-26 showed more radiopacity and flow compared to two other experimental sealers (P<0.05). However, both sealers had lower setting time than AH-26 (P<0.05). No statistical differences were found regarding film thickness, solubility and radiopacity (P>0.05). The characterization analysis exhibited relatively similar microstructure of AH-26 sealer to the experimental root canal sealers. Conclusion: According to the result of this study, all tested root canal sealers had acceptable properties based on ISO 6876 standard criteria. Keywords: Epoxy Resin; Fourier Transform Infrared; Root Canal Sealer; Scanning Electron Microscopy; X-Ray Energy Dispersive Spectroscopy